Scheduling irrigation in a selected Panam canal command in Panchmahal district for optimum water use - KUMAR, DEEPAK; TIWARI, M. K. (Journal of Soil and Water Conservation, 2020)
The irrigation scheduling needs to be carried out with the objectives of improving the system operation. The study was undertaken to assess the actual irrigation scheduling of the Panam Irrigation Project (PIP). Periodic volumetric gross irrigation requirement was estimated by using standard methodology. Daily water delivery of 29-R distributary during the period 2015-16 was collected from potential sources and analysed. Periodic water supply was considered as fixed and sowing time was either advanced or delayed. The water supply and demand was analysed on 10 days basis by considering the prevailing cropping practices as well as five more strategies such as one 10 days advance, one 10 days delayed, two 10 days delayed, one fortnightly advanced and one fortnightly delayed. The supply-demand ratio was then compared to find out the best strategy under the prevailing water supply situations. The one 10 days advanced schedule shows comparatively better performance. Hence, this schedule can be practiced for enhancing the water use efficiency. As the supply based strategy shows wide variability in supply, demand and supply-demand ratio, hence, demand based strategy needs to be incorporated in the selected command area.